Estimation of growth parameters for the exploited sea cucumber Holothuria arguinensis from South Portugal - Olaya-Restrepo, Julian (2018)
Understanding how species grow is critical for choosing appropriate fisheries management strategies. Sea cucumbers shrink during periods of aestivation and have naturally flaccid bodies that make measuring growth difficult. In this study, we obtained length-frequency data on Holothuria arguinensis, measuring undisturbed animals in situ, because it is one of the new target species of the NE Atlantic and Southwestern Mediterranean fisheries. Growth parameters were estimated for individuals inhabiting the Ria Formosa lagoon (Portugal). Length-frequency data were collected between November 2012 and March 2014 by using a visual census augmented with random sampling in 2014. To estimate the asymptotic length (L-infinity) and growth coefficient (K), 2 different growth models were fitted to the length frequency data for 1198 sea cucumbers: the nonseasonal von Bertalanffy and Hoenig seasonal von Bertalanffy models. A L-infinity of 69.9 cm and K of 0.88 were estimated by using the Hoenig function for seasonal growth. The value of 1.0 obtained for the parameter C of this function indicates reduction in growth during winter. The relatively high growth rate (K) of this species may have important implications for its survival, mainly in environments where conditions cause biological stress and oceanic disturbances but may also increase its potential as a candidate for aquaculture.